Critical Discourse Analysis of Barack Obama Speech - Dwi Martika; Mahyuni; Atri Dewi Azis (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2022)
Critical Discourse Analysis is often applied to analyze political discourse including public speaking. The analysis of this thesis is based on a theory of CDA and its analysis methods which were represented by Thomas N. Huckin. Whereas the discussion used the descriptive qualitative research method which deals with data that are in the form of words, rather than statistics and attempts to arrive at a rich description of something systematically. It starts by analyzing some features in the text as a whole. Then, it is continued by analyzing some features at sentence-level and word levels. Since it is a critical discourse, therefore those features are analyzed critically. In a fact, it is found a deficiency in analyzing each feature based on the speech of Obama. The last is by doing contextual interpretation; it is summarized what language expression is used by Obama to uncover power and ideology. The interpretation is also based on the results from the two previous analyses. The result shows that CDA can explore the relationships between language, power, and ideology. Through the language used, it can be known the strength of power and the purpose of the speaker, which the power is strongly felt, and the ideology is seen as well as understandable.